(untitled) (Kairaranga, 2016)
The current study aims to review the literature regarding Tier Two behavioural interventions for children aged 5 to 13, and identify the core components which the research suggests are important to their effectiveness and/or social validity. Trends within the research indicate schools are more likely to adapt interventions to fit their own school context or meet what is socially valid to their teachers, students, and community, as opposed to implementing an intervention with excellent (empirically-based) fidelity. Through compiling the best-practice components of Tier Two interventions, a checklist has been created for schools to use when they are making adaptation to interventions, or developing their own. This supports the approach schools are already taking, promotes flexibility, and allows schools the space to develop cultural and social relevancy in Tier Two interventions; while still incorporating the components of what the wider literature advocates is effective with at-risk students.